How do you multiply (x+3)(x-3)+(x+7)(x-3)?

1 Answer
Feb 13, 2016

color(blue)(2x^2+4x-30)

Explanation:

We can use the FOIL Method,
(First, Outer, Inner, and Last)

like this,

(a+b)(c+d) = ac + ad + bc + cd

Solving the problem,

(x+3)(x-3) + (x+7)(x-3)

we can simplify the 1st term, (x+3)(x-3)

(x+3)(x-3) = x^2 -3x+3x-9

x^2 -3x+3x-9, combine all like terms, to simplify, if there is any, like -3x and +3x, we can combine this.

Since a + (-a) = 0 (Additive Inverse Property), we can cancel the like terms giving,

= x^2 - 9

now apply FOIL method, to the 2nd term.

(x+7)(x-3) = x^2-3x+7x-21

simplify, by combining like terms,

= x^2+4x-21

Plug it all,

x^2 - 9 + x^2+4x-21

combine like terms to simplify again, we must simplify the answer as long as possible.

= 2x^2+4x-30